Korzyści wynikające z funkcjonowania spółek przemysłu cukierniczego na rynku giełdowym - Szybiga, Krystyna (Benefits of the Functioning of Confectionary Industry Companies on a Share Market, 2006)
Confectionary industry belongs to a dynamically developing market, and companies of this trade were privatised and sold in the first place to foreign investors. They also belong to capital market pioneers. Actually on Warsaw Stock Exchange (WSE) are three confectionary companies, namely: Jutrzenka, Mieszko and Wawel, which brands are well recognized on the market. Financial results are differentiated and closely combined with managers' skill. Capitalisation companies as a result of shares emission on WSE made investments and company development possible.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 399-404